Oral Health Status, Salivary MMP-8& Secretory Leukocyte Peptidase Inhibitor (SLPI) Among Uncontrolled Type-I Diabetes Mellitus In Iraqi Patients - Ahmed, Rehab F; Al-Jubouri, Raja H (Journal of Baghdad College of Dentistry, 2017)
Background: diabetes is a metabolic disease characterized by hyperglycemia that results in deficiency or absence of insulin production. The dental caries and gingivitis/periodontitis are widespread chronic diseases in diabetes. The aim of the present study was determined the salivary matrix metalloproteinase (MMP-8), Secretory Leukocyte Peptidase Inhibitor (SLPI) and oral health status among uncontrolled diabetic group in comparison with healthy control group.Materials and Methods: The total sample composed of 90 adults aged (18-35) years. Divided into 60 uncontrolled diabetic patients (HbA1c >7%) and 30 healthy control group. Unstimulated saliva was collected from each subject with type-I DM, BMI, duration of diabetes, HbA1c%, DMFT, gingival index (GI) and periodontal disease index were recorded during clinical visit. Level of salivary MMP-8 and SLPI was measured by using ELISA immunoassay analysis. Results: The DMFT was highly significant higher among type-I DM group than control group (p